Acute haematogenous osteomyelitis in Lisbon: an unexpectedly high association with myositis and arthritis - Catarina Gouveia; Joana Branco; Susana Norte; Joana Arcangelo; Pedro Alves; Margarida Pinto; Delfin Tavares (Elsevier, 2022)
Introduction: Despite the current trend toward less aggressive therapeutic approaches, acute haematogenous osteomyelitis (AHO) continues to be a challenge and is associated with significant morbidity worldwide. Our aim was to assess whether compliance with the current protocol was achieved in 80% of cases, to identify complications and the associated risk factors, and to analyse trends in the aetiology and management of AHO in the paediatric population. Methods: We conducted a longitudinal, observational, single-centre study in patients with AHO aged less than 18 years admitted to a paediatric hospital between 2008 and 2018 divided in 2 cohorts (before and after 2014). We analysed data concerning demographic and clinical characteristics and outcomes. Results: The study included 71 children with AHO, 56% male, with a median age of 3 years (interquartile range, 1-11). We found a 1.8-fold increase of cases in the last 5 years. The causative agent was identified in 37% of cases: MSSA (54%), MRSA (4%), S. pyogenes (19%), K. kingae (12%), S. pneumoniae (8%), and N. meningitidis (4%). Complications were identified in 45% of patients and sequelae in 3.6%. In recent years, there was an increase in myositis (30% vs 7%; P = .02), septic arthritis (68 vs 37.2%; p = 0.012) and in the proportion of patients treated for less than 4 weeks (37 vs 3.5%; p = 0.012), with a similar sequelae rates. The risk factors associated with complications were age 3 or more years, C-reactive protein levels of 20 mg/L or higher, time elapsed between onset and admission of 5 or more days and positive culture, although the only factor that continued to be significantly associated in the multivariate analysis was positive culture. The presence of complications was a risk factor for sequelae at 6 months. Conclusions: Our study confirms that AHO can be aggressive. The identification of risk factors for complications is essential for management. Resumen: Introducción: Aunque actualmente se tiende a un abordaje terapéutico menos agresivo, la osteomielitis hematógena aguda (OHA) sigue suponiendo un reto, con una morbilidad significativa a nivel mundial. El objetivo del estudio fue evaluar si se alcanzó una adherencia del 80% con el protocolo vigente, identificar las complicaciones y riesgos asociados y analizar las tendencias en la etiología y el manejo de la OHA en la población pediátrica. Métodos: Estudio observacional longitudinal unicéntrico en pacientes menores de 18 años con OHA ingresados en un hospital pediátrico entre 2008 y 2018 divididos en 2 cohortes (antes y después de 2014). Se analizaron datos demográficos, clínicos y concernientes a la evolución de la enfermedad. Resultados: El estudio incluyó a 71 niños con OHA, 56% varones, con una edad mediana de 3 años (rango intercuartílico, 1-11). Se observó una incidencia 1.8 veces mayor en los últimos 5 años. El agente causal se identificó en el 37% de los casos: SASM (54%), SARM (4%), S. pyogenes (19%), K. kingae (12%), S. pneumoniae (8%) y N. meningitidis (4%). Se identificaron complicaciones en el 45% y secuelas en 3.6% de los pacientes. En los últimos años aumentó la incidencia de miositis (30% vs 7%; p = 0,02) y de artritis séptica (después de 2015, 68 vs 37.2%, p = 0,012), así como la proporción de pacientes con tratamiento inferior a 4 semanas (37 vs 3.5%; p = 0,012), con tasas de secuelas similares. Los factores de riesgo de complicaciones fueron la edad ≥ 3 años, nivel de Proteina C-reactiva ≥ 20 mg/L, duración de los síntomas al ingreso de 5 o más días y cultivo positivo, aunque en el análisis multivariado solo se validó el cultivo positivo. La presencia de complicaciones se identificó como factor de riesgo de secuelas a los 6 meses. Conclusiones: El presente estudio confirma que la OHA puede ser agresiva. La identificación de los factores de riesgo es fundamental para su abordaje.